RESCRIEREA TRECUTULUI PRIN FILTRUL PROZEI ROMANTICE ÎN ROMANUL ROMÂNESC CONTEMPORAN (Analele Universității București. Limba și literatură română, 2025)
The present article aims at deciphering some of the functions and meanings of the so-called historical turn in Romanian contemporary fiction. In this attempt, we’ll analyse two recently published novels, Mircea Cărtărescu’s Theodoros (2022), respectively Simona Antonescu’s Chiajna din Casa Muşatinilor (2023), that can be read not only as “exoticized” representations of the past, but also as parables that reflect upon the consequences entailed by the obsession with exercising absolute power.